Food Authentication: Techniques, Trends and Emerging Approaches (Second Issue) (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The authentication of foods and beverages is a very current topic of great interest for all the actors involved in the food chain, including the food industry, consumers, and food science researchers. Food authenticity covers many different aspects related to mislabeling, adulteration, and misleading claims about origin, production methods, or processing technologies. As many factors may affect the chemical composition of foods (e.g., geographical origin, variety or breed, conditions of cultivation, and breeding and/or feeding), the implementation of accurate, robust, and high-throughput analytical methods is needed to assess their authenticity and traceability and, consequently, guarantee their safety and quality in terms of organoleptic, nutritional, and bioactive characteristics. For these purposes, multiple analytical tools can be employed in combination with advanced chemometrics, such as spectroscopic and chromatographic techniques, DNA-based methods, and state-of-the-art omics approaches. In this context, in 2020, the journal Foods launched the Special Issue “Food Authentication: Techniques, Trends and Emerging Approaches” to gather research papers and review articles dealing with the development and application of analytical techniques and emerging approaches in food authentication. Considering the success and popularity of this earlier Special Issue, we will now release a second Special Issue comprising ten valuable scientific contributions, including one review article, one commentary article, and eight original research articles.